(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Bus drivers are a vulnerable population due to their unhealthy lifestyle and poor sleeping habit. Bus driving is a responsible skilled job which requires keen attention to the immediate surrounding which makes them stressed physically and mentally every day. Stress is inevitable among bus drivers and the sleep, stress, and depression form a vicious cycle which leads to serious health impact among the drivers. With this view, this study was conducted with the aim of assessing the impact of stress on health status among Tamilnadu State Transport Corporation (TNSTC) bus drivers in the Perambalur district. Materials and Methods: A cross-sectional study was done from 1st March 2019 to 30th July 2020, with universal sampling in Perambalur bus depot among 203 Tamil Nadu State Transport Corporation (TNSTC) bus drivers. The data was collected by using a semi-structured questionnaire. The stress was assessed by using Perceived Stress Scale (PSS-10), Depression assessed by using Patient Health Questionnaire-9 (PHQ-9), and sleep deprivation assessed by using Epworth Sleepiness Scale (ESS). Results: The prevalence of perceived stress, depression, and daytime sleepiness among government bus drivers is 23%, 26%, and 25% respectively. The risk factors that have a statistically significant association with increased perceived stress are using spectacles while driving, smoking more than five cigarettes per day, having Driver-Conductor conflict, not received the non-accident certificate, poor sleep, and moderate depression. Conclusion: The prevalence of stress, depression, and sleep deprivation are very high among government bus drivers. Preventing stress and promoting mental health is essential to reduce the vulnerability among government bus drivers.